2022
DOI: 10.1007/s00127-022-02372-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of postpartum depression among women living in the United Arab Emirates

Abstract: Purpose Postpartum depression received almost no attention in the United Arab Emirates (UAE). The aim was to examine the prevalence of depressive symptomatology and the associated risk factors among women in the UAE. Methods A prospective cohort study recruited women from postpartum wards in hospitals across four emirates in the UAE. Women completed questionnaires immediately after childbirth and at 3 and 6 months postpartum. Depressive symptomatology was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…Scheyer and Urizar (2016) suggest that high perceived stress across pregnancy trimesters and 3 months postpartum are associated with increased PPD risk for low‐income women (Scheyer & Urizar, 2016). This finding is corroborated by recent research also suggesting that low income is associated with increased PPD risk (Hanach et al, 2023). Moreover, studies suggest that PPD is two to four times more common for low‐income women compared to middle‐ and upper‐income women.…”
Section: Introductionsupporting
confidence: 85%
“…Scheyer and Urizar (2016) suggest that high perceived stress across pregnancy trimesters and 3 months postpartum are associated with increased PPD risk for low‐income women (Scheyer & Urizar, 2016). This finding is corroborated by recent research also suggesting that low income is associated with increased PPD risk (Hanach et al, 2023). Moreover, studies suggest that PPD is two to four times more common for low‐income women compared to middle‐ and upper‐income women.…”
Section: Introductionsupporting
confidence: 85%
“…A total score of ≥13 is considered indicative of PPD, with a significant increase in specificity of 0.95 (20). EPDS was commonly used to assess the degree of PPD, and many studies reported good validity and reliability of the Edinburgh tool in different contexts, from 0.76 to 0.861 (21,22), and The Cronbach's alpha of EPDS in this study was 0.853.…”
Section: Edinburgh Postpartum Depression Scalementioning
confidence: 53%
“…A previous study also found that relationship quality and partner support were predictors of PPD [ 31 ]. Another study showed that spousal support was associated with a reduced risk of PPD [ 32 ].…”
Section: Discussionmentioning
confidence: 99%